An integrative review of drug utilization by the elderly in primary health care - Luciane Paula Batista Araújo de Oliveira; Sílvia Maria Azevedo dos Santos (SciELO, 2016)
ABSTRACT OBJECTIVE To identify knowledge produced about drug utilization by the elderly in the primary health care context from 2006 to 2014. METHOD An integrative review of the PubMed, LILACS, BDENF, and SCOPUS databases, including qualitative research papers in Portuguese, English, and Spanish. It excluded papers with insufficient information regarding the methodological description. RESULTS Search found 633 papers that, after being subjected to the inclusion and exclusion criteria, made up a corpusof 76 publications, mostly in English and produced in the United States, England, and Brazil. Results were pooled in eight thematic categories showing the current trend of drug use in the elderly, notably the use of psychotropics, polypharmacy, the prevention of adverse events, and adoption of technologies to facilitate drug management by the elderly. Studies point out the risks posed to the elderly as a consequence of changes in metabolism and simultaneous use of several drugs. CONCLUSION There is strong concern about improving communications between professionals and the elderly in order to promote an exchange of information about therapy, and in this way prevent major health complications in this population.